The Effect of Extensive Reading Courses on Vocabulary Improvement in ELED Students - Pua, Sri Dayana; Otoluwa, Moon H; Mamu, Rahmawaty (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
This study aims to determine the effect of applying the Extensive Reading method on improving English vocabulary mastery among seventh-grade students at SMP Negeri 12 Sipatana. Vocabulary mastery is an important aspect of English language skills, which underlies the ability to read, write, speak, and listen. The Extensive Reading method is considered effective because it provides broad and contextual language input through enjoyable free reading activities that are in line with students' interests. This study used a quantitative approach with a pre-experimental design of the one group pre-test and post-test type. The sample in this study consisted of 23 seventh-grade students selected through purposive sampling. The research instrument was a multiple-choice test consisting of 50 questions covering four parts of speech (nouns, verbs, adjectives, and adverbs). The data were analyzed using a paired sample t-test through the SPSS version 23 program. The results showed a significant increase in the post-test average score (60.30) compared to the pre-test (56.47). The statistical test showed a significance value of 0.000 0.05, which means Ho was rejected and Ha was accepted. Thus, it can be concluded that the Extensive Reading method has a positive and significant effect on improving students' vocabulary mastery. These findings support that Extensive Reading can be an effective alternative learning strategy to increase students' motivation and vocabulary skills in English learning at the junior high school level..